A 28-Day Challenge to Help Quit Smoking Using Telephone Follow-Ups Combined With the WeChat App: The Impact of the Humanistic Approach on Smoking Cessation. Issue 3 (July 2021) - Zhang, Sisi; Ding, Qian; Shen, Jun; Qu, Heming; Meng, Xiaoping
Abstract: The study aims to assess the effectiveness of telephone follow-ups combined with a smartphone app (e.g., WeChat [Tencent], which is one of the most widely used communication apps in China), as a smoking cessation intervention. Social volunteers were recruited on March 1, 2017, and randomized to supervision groups with five participants in each group. Every day, the specialists shared some information related to smoking cessation including the videos, songs, and scientific knowledge in WeChat groups and conducted telephone follow-ups on the third, fifth, seventh, ninth, 12th, 17th, 22nd, 27th, and 30th day in March and on April 1. Ultimately, a comparison was made of the self-reported smoking abstinence and self-reported average number of cigarettes smoked between the participants. One hundred ten volunteers participated in the study, with 105 who completed follow-up. Self-reported smoking abstinence in the past 7 days occurred in 65.7% of the participants ( n = 69) compared with 34.3% ( n = 36) in whom smoking abstinence did not occur. The mean age of those who failed was 40.15 years (range: 22–70 years), and 55.5% ( n = 20) attributed their failure to personal reasons. However, the self-reported average number of cigarettes smoked every day was less than that before the study (on average, 10.34 ± 8.17 per day), and this difference was statistically significant (95% CI [8.312, 12.364], p < .01). It was effective to deliver a telephone follow-up combined with a smartphone app follow-up as an intervention for smoking cessation.